Review Paper: The Bed Incline and Prevention of Ventilator-Associated Pneumonia - Tahereh Najafi Ghezeljeh; Leila Kalhor (Iran University of Medical Sciences, 2016)
Background: Ventilator-Associated Pneumonia (VAP) is the most common nosocomial (hospital acquired) infection among patients undergoing mechanical ventilation. It increases mortality rate, duration of mechanical intubated ventilation, and hospitalization in the Intensive Care Units (ICUs). This review study aims to determine the proper gradient of a hospital bed in preventing VAP in patients hospitalized in ICUs. Methods: In this study, research articles published from 1999 to 2016 were searched in PubMed, Science Direct, SID, and library sources, using keywords of "ventilator-associated pneumonia" and "elevated bed incline" and their corresponding terms in the Persian language. Results: Results of the review showed that limited studies have been conducted on comparing the different inclines of bed and their effects on preventing VAP. Also, the available studies had methodological limitations or hospital staff failed to keep the patient in the same bed incline which was under the study for prolonged duration. Based on 19 reviewed studies, the incidence of VAP, hospital costs, mortality rate, and duration of mechanical ventilation in patients whose beds were inclined at 45 degrees or 30-45 degrees were significantly lower compared to patients reclining in the supine position. Although, in most conducted studies there were no consensus over a suitable bed incline in prevention of VAP and bedsore. Conclusion: Raising the incline of bed can play a role in lowering the incidence of VAP, mortality rate, hospital costs and duration of mechanical ventilation. However, the proper gradient is not definite and requires studies with proper methodology in this regard.